2016
DOI: 10.4187/respcare.04574
|View full text |Cite
|
Sign up to set email alerts
|

The Severe Respiratory Insufficiency Questionnaire for Subjects With COPD With Long-Term Oxygen Therapy

Abstract: BACKGROUND: Respiratory insufficiency in COPD may present as hypoxic and/or hypercapnic respiratory failure treated with long-term oxygen therapy (LTOT) and/or noninvasive ventilation (NIV) with LTOT. The Severe Respiratory Insufficiency Questionnaire (SRI) is a tool for the assessment of health-related quality of life (HRQOL) in subjects receiving NIV. However, it remains unclear whether the SRI is also capable of assessing and discriminating HRQOL in subjects receiving LTOT. METHODS: Stable subjects with COP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
(43 reference statements)
2
14
0
1
Order By: Relevance
“…Thus, structurally, the SRI would measure diversified health impairments more discriminatively than the MRF-26, although it may take more time to be administered. While the MRF was developed for patients with chronic respiratory failure irrespective of NIV, the SRI was primarily developed for patients with home NIV, and it recently was validated in patients with COPD receiving long-term oxygen therapy [18]. As a limitation of the present study, we did not compare responsiveness of the questionnaires, and this should be studied in the near future.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, structurally, the SRI would measure diversified health impairments more discriminatively than the MRF-26, although it may take more time to be administered. While the MRF was developed for patients with chronic respiratory failure irrespective of NIV, the SRI was primarily developed for patients with home NIV, and it recently was validated in patients with COPD receiving long-term oxygen therapy [18]. As a limitation of the present study, we did not compare responsiveness of the questionnaires, and this should be studied in the near future.…”
Section: Discussionmentioning
confidence: 95%
“… 14 28 In addition, we will assess the criterion validity of the SRI questionnaire in a future study. Recently, Windisch et al 28 showed that the SRI questionnaire was valid for patients with COPD receiving long-term home oxygen therapy. Therefore, in the near future, we plan to assess the reliability and validity of the Chinese version of the SRI questionnaire in patients with chronic hypercapnic respiratory failure who also have other diseases requiring long-term home mechanical ventilation and in patients with COPD receiving long-term home oxygen therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We did all blood gas measurements from arterialized capillary blood during spontaneous breathing, at least 1 h after the patients in the intervention group had switched from NPPV to spontaneous breathing. We assessed HRQL using the Severe Respiratory Insufficiency (SRI) Questionnaire14,15 and the COPD assessment test (CAT) as tools. We estimated pulmonary function, 6-min walk distance (6MWD), blood oxygen saturation, baseline dyspnea index (BDI), and transition dyspnea index (TDI) as previously specified 1618.…”
Section: Methodsmentioning
confidence: 99%